The influence of natural environments on creativity - Yeh, Chin-Wen; Hung, Shih-Han; Chang, Chun-Yen (Frontiers in Psychiatry, 2022)
This study investigated the effects of different natural environments on attention restoration and creativity. To compare the restorative benefits based on the degrees of perceived naturalness in urban areas, this study categorized environments into three types of perceived naturalness and tested the effect on one’s creativity. The urban campus was selected as the study site, representing high-, medium-, and low-perceived naturalness photosets downloaded from Google Street Map images as experimental stimuli. The study invited 100 subjects to take the Abbreviated Torrance Test for Adults (ATTA), which measures creative thinking by viewing the onscreen photosets of the experimental stimuli. In addition, this study asked participants to complete psychological questionnaires, including the Perceived Restoration Scale (PRS) and the Inspiration Scale (IS). The results showed that high- and medium-perceived naturalness in the urban-campus site was superior to low-perceived naturalness in creative performance. In addition, there were significant differences in elaboration and flexibility for different degrees of perceived naturalness. Various degrees of perceived naturalness showed a substantial correlation between PRS scores and ATTA scores. The attention restoration benefits of high- and medium-naturalness environments improve creativity. Our study indicates that viewing natural environments stimulates curiosity and fosters flexibility and imagination, highly natural environments distract our minds from work, and the benefits of attention restoration can improve the uniqueness and diversity of creative ideas. This study provides a reference for creative environmental design and supports further understanding of nature’s health and creativity benefits in urban areas.